Functional genomic investigation of CYP71AJ49 in Peucedanum praeruptorum Dunn: Agrobacterium-mediated overexpression reveals dual roles in drought adaptation and coumarin biosynthesis - Wang, Maosuo; Wang, Shenghua; Chu, Huifang; Ruan, Qian; Dai, Jun; Wei, Peipei (Frontiers in Plant Science, 2025)
IntroductionDrought stress is one of the major limiting factors for plant growth and agricultural production worldwide. This study seeks to investigate the role and mechanism of CYP71AJ49, a key enzyme gene in the coumarin biosynthesis pathway, under drought stress, and to elucidate its dual functions in drought tolerance and coumarin synthesis.MethodsCYP71AJ49 was isolated and cloned from Peucedanum praeruptorum Dunn, and heterologously overexpressed in Arabidopsis thaliana. Drought stress was mimicked with 20% PEG, after which transcriptome sequencing, analysis of physiological and biochemical parameters (including root length, fresh weight, antioxidant enzyme activities, proline, and malondialdehyde), and qRT-PCR validation were performed. Furthermore, coumarin content was quantified using ultra-performance liquid chromatography.ResultsOur findings demonstrated that overexpression of CYP7IAJ49 remarkably improved the drought tolerance of Arabidopsis thaliana. Under drought stress, transgenic plants exhibited significant increases in root length (22.84%), fresh weight (164.91%), and water content (294.41%). Simultaneously, their carbohydrate metabolism pathway was activated, the transcription levels of stress-responsive genes were upregulated, antioxidant enzyme activities and proline content were significantly enhanced, while malondialdehyde content was substantially decreased. Furthermore, CYP7IAJ49 also significantly promoted the accumulation of bergapten (52.42%) in Arabidopsis thaliana.DiscussionOur findings demonstrate that CYP71AJ49 improves plant drought resistance through multiple pathways while regulating the accumulation of coumarin secondary metabolites. This discovery not only expands our understanding of the functions of CYP450 family genes but also provides critical theoretical support and genetic resources for breeding new crop varieties with high drought tolerance and high coumarin content.